Ab initio study of cyclohexane dehydrogenation with a transition metal (Pt, Pd, Ni and Cu) atom - Tsuda, Muneyuki (Animo Repository, 2004)
To investigate cyclohexane dehydrogenation by a transition metal M (M: Pt, Pd, Ni and Cu) atom, we perform total energy calculations, based on the density functional theory. We consider the process where cyclohexane approaches the M atom. Upon interacting with the M atom, the M atom draws an H atom from the cyclohexane, forming an H-M bond. With a broken C-H bond, the dehydrogenated cyclohexane separates from the M atom. Of the M elements we investigated, a Pt atom exhibited the highest reactivity. In breaking the C-H bond of the cyclohexane, the σ donation dominates for a Pd and Cu atom as compared with the Pt atom, and the π back-donation dominates for a Ni atom as compared with the Pt atom. The results indicate that the excess charge transfer requires more energy for breaking the C-H bond of the cyclohexane with the Pd, Ni and Cu atom. ©2004 The Physical Society of Japan.